Quercus rajushkinae, a new name for Quercus lavrovii Rajushkina (Fagaceae) - Doweld, Alexander Borisovitch (Phytotaxa, 2015)
The fossil species Quercus lavrovii Rajushkina (1987: 146) was described on the fossil leaf remains of an oak from the Miocene sediments of Dzhungarian Aktau, Ili depression (Kazakhstan, Central Asia). However, according to Art. 53.1 of ICN (McNeill et al. 2012) this name is illegitimate because of the existence of an overlooked earlier homonym, Quercus lavrovii Budantsev (1955: 93) which was originally described from the earlier Oligocene deposits of Bestau, Turgay (Kazakhstan). The homonymy between these fossil species emerged during the creation of the International Fossil Plant Names Index, which is planned to list all fossil plant species (IFPNI 2014 onwards). Since the preoccupied species P. lavrovii Rajushk. is systematically recognized as a valid species in current use and it does not have any synonym, a nomen novum, Q. rajushkinae, is here formally proposed as a replaced name.